An association between arterial pulse pressure and variation in the fibrillin-1 gene. Issue 4 (1st October 1997) - Powell, J T; Turner, R J; Henney, A M; Miller, G J; Humphries, S E
Abstract : Objective: To investigate whether variation in the fibrillin-1 gene was associated with blood pressure in healthy middle aged men, as had been observed in patients with abdominal aortic aneurysm. Design, setting, and patients: Middle aged men (n = 245), aged 50 to 61 years, were recruited from one of the nine general practices participating in the second Northwick Park heart study. Blood samples were obtained for the preparation of genomic DNA and analysis of plasma variables. Main outcome measures: Systolic, diastolic, and pulse pressures; fibrillin-1 genotype characterised with a four allele variable tandem nucleotide repeat polymorphism in intron 28. Results: In healthy middle aged men only three common genotypes were observed: 2-2 (frequency 54.1%), 2-3 (16%), and 2-4 (15%). The mean arterial systolic (and pulse) pressure varied according to fibrillin-1 genotype: 2-4 genotype, 126.3 (47.6) mm Hg; 2-2 genotype, 131.0 (51.3) mm Hg; and 2-3 genotype, 135.5 (54.2) mm Hg. The median pulse pressure was 50 mm Hg. Distribution of men around the median pulse pressure, according to genotype, showed a significant trend for patients of 2-4 genotype to have the lowest pulse pressures, those of 2-2 genotype to have intermediate pressures, and those of 2-3 genotype to have the highest pulse pressures (p = 0.003 for healthy men). Conclusions: There appears to be a significant association between fibrillin-1 genotype and arterial pulse pressure in men aged 50 to 61 years.